Upaya Meningkatkan Kemandirian Dan Prestasi Belajar Matematika Melalui Model Pembelajaran Inkuiri - Emah Sri Haryanti; Sri Muryaningsih (Departement of Mathematics Education, 2024)
This research is motivated by the low level of student learning independence which results in unsatisfactory learning achievement. Therefore, it is necessary to develop innovative learning models in mathematics learning to increase student independence and learning achievement. The aim of this research is to describe the level of independence and achievement in learning mathematics on the topic of fractions using the Inquiry learning model. The subjects of this research were 29 fifth grade students. This research was carried out in two cycles, with two meetings in each cycle. Data is collected through teacher observation, student observation, and tests at the end of each cycle. The research results showed that the average value of learning outcomes increased from 57.85% in the pre-cycle to 65.18% in the first cycle, then increased again to 81% in the second cycle. The percentage of students' classical completeness also increased from 59.25% in the first cycle test to 88.20% in the second cycle final test, exceeding the classical completeness target set at 80%. Apart from that, the level of student learning independence also experienced a significant increase from 34.48% in cycle 1 to 86.20% in cycle 2. Thus, it can be concluded that the inquiry learning model is effective in increasing students' independence and mathematics learning achievement. fifth grade students at state elementary school 1 Kejobong.